A bibliometric analysis and literature review on emotional skills - Manjarres, María Teresa; Duarte, Diana Paola Mahecha; Navarro-Obeid, Jorge; Álvarez, Maria Laura Vergara; Martinez, Isneila; Cudris-Torres, Lorena; Hernández-Lalinde, Juan; Bermúdez, Valmore (Frontiers in Psychology, 2023)
The content, management, and implementation of social skills have been developed since the end of the 20th century as a model of capabilities. Thus, as human beings develop and train their basic cognitive and perceptual–motor functions, they increase their ability to solve and cope with difficulties. This article aims to present a bibliometric and systematic review of social skills, using query sources in databases such as Web of Science (WoS) and Scopus between the years 2000 and 2022, with platforms such as Bibliometrix and Gephi. This search yielded a total of 233 records in WoS and 250 records in Scopus that were merged and, after eliminating 143 duplicate data, were consolidated into 340 records that enclose the academic production of 20 years. Through scientific mapping, the main authors, journals, and countries in this field were determined; similarly, the most relevant studies were classified into three categories, namely, classic, structural, and perspectives, which were represented by means of the metaphor of the tree of science. In addition, a program for further studies was planned, such as in-depth qualitative research measuring observationally and directly taking into account emotional expressiveness, emotional understanding, emotion regulation, and behavior, and the impact of social skills training on social problem-solving. Finally, another important aspect to mention is that this research work is useful for the scientific academic community in many areas of knowledge such as psychology, education, and managers of educational institutions.